The “beauty premium” effect of voice attractiveness of long speech sounds in outcome-evaluation event-related potentials in a trust game - Shang, Junchen; Liu, Zhihui (Frontiers in Psychology, 2022)
Previous research suggested that people with attractive voices had an advantage in economic games, even if the voices were only presented for 400 ms. The present study investigated the influence of voice attractiveness on the cooperative trust behavior with longer exposure times to the voices. Event-related potentials (ERPs) were recorded during the feedback outcome evaluation. Participants heard a voice of the partner for 2,040 ms and decided whether to invest to the partner for a possibility to gain more money. The results showed that participants made more invest choices to the attractive partners, replicating the “beauty premium” effect of the attractive voices. Moreover, participants were more likely to invest to male partners. The ERP analysis for the outcome showed that the difference waves of feedback-related negativity (FRN) amplitude were smaller in the attractive voice condition than in the unattractive voice condition, suggesting that the rewarding effect of attractive voices weakened the frustrating feelings of the loss. In sum, the present study confirms that attractive voices with longer presentation durations facilitate cooperative behavior and modulate the processing of feedback evaluations.